Effect of irrigation scheduling and nitrogen management on growth and development of Indian mustard (Brassica juncea) - NARAGUND, RUXANABI; PATEL, R A; SINGH, Y V; KADAM, PRAVEEN; R, PRAVEEN B (The Indian Journal of Agricultural Sciences, 2023)
A field experiment was conducted during winter (rabi) seasons of 2019–20 and 2020–21 at Agronomy Farm, Anand Agricultural University, Anand, Gujarat to assess the influence of irrigation scheduling and nitrogen management on crop growth and development of Indian mustard [Brassica juncea (L.) Czern]. The experiment was planned using split-plot design where treatments replicated thrice. The main plots were allotted with 3 irrigation levels, viz. irrigation at 0.6 IW/CPE ratio (I1), irrigation at 0.8 IW/CPE ratio (I2) and irrigation at 1.0 IW/CPE ratio (I3) and in sub-plots 5 nitrogen management treatments, viz. 100% RDN through chemical fertilizer (N1); 100% RDN through vermicompost (N2); 75% RDN through chemical fertilizer + 25% RDN through vermicompost (N3); 50% RDN through chemical fertilizer + 50% RDN through vermicompost (N4) and 25% RDN through chemical fertilizer + 50% RDN through vermicompost + Bio NPK Consortium @1.0 litre/ha (N5) were practised. The results showed that, growth traits of mustard, viz. height of plant, dry matter accumulation, crop growth rates, leaf area and leaf area index were significantly enhanced by scheduling irrigation at 0.8 IW/CPE ratio and application of 50% RDN through chemical fertilizer + 50% RDN through vermicompost among nitrogen management treatments. Hence, mustard growth and development can be significantly improved by application of irrigation at 0.8 IW/CPE ratio and 50% RDN through chemical fertilizer + 50% RDN through vermicompost.